Evolution of a Wingless Gene and its Utility for Inferring the Relationships within Glyphodes Moths - HARI SUTRISNO (Bogor Agricultural University, Indonesia, 2006)
The evolution of a nuclear Wingless gene was investigated and its utility for inferring the phylogenetic relationship within Glyphodes moths was assessed by comparing with other three genes namely, COI, COII, and EF-1?. The results show that the bias of base compositions in Wingless (C: 0.19) is the lowest among those in COI, COII, and EF-1?. The averages of nucleotide sequence divergences for comparison between groups based on the Wingless were the highest. While substitutions in Wingless and EF-1? genes were not saturated at the divergence of the species groups, COI and COII genes attained saturation at those levels. The phylogenetic analysis based on Wingless solely show that this gene was very useful to resolve the relationships between groups but gave a poor resolution at the specific level, i.e. the relationships within group 1 was not resolved. Combination of all data supports the phylogenetic hypothesis based on morphological data. Glyphodes falls into three species groups: group 2 branched off first then followed by groups 1 and 3. Key words: COI, COII, EF-1?, genes, Glyphodes, mitochondria, moth, phylogeny, relationships, Wingless